2017
DOI: 10.1016/j.kint.2016.12.013
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis suggests obesity predicts onset of chronic kidney disease in the general population

Abstract: Obesity and chronic kidney disease (CKD) are public health priorities that share core pathophysiological mechanisms. However, whether high body mass index (BMI) increases risk of CKD de novo remains ill-defined. To evaluate the role of BMI in predicting CKD onset in the general adult population, we performed a systematic review and meta-analysis of PubMed and ISI Web of Science databases articles published between January 2000 and August 2016 without language restriction. We selected studies in adult individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
225
4
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 279 publications
(240 citation statements)
references
References 69 publications
8
225
4
3
Order By: Relevance
“…Obesity has been thought to have a negative effect on mortality because of its close association with various metabolic diseases . However, recent studies have consistently suggested that body fat distribution may be more important than overall adiposity .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Obesity has been thought to have a negative effect on mortality because of its close association with various metabolic diseases . However, recent studies have consistently suggested that body fat distribution may be more important than overall adiposity .…”
Section: Discussionmentioning
confidence: 99%
“…Obesity has been thought to have a negative effect on mortality 6 because of its close association with various metabolic diseases. [3][4][5] However, recent studies have consistently suggested that body fat distribution may be more important than overall adiposity. [14][15][16][17] There have been several efforts to differentiate body fat by its deposited location to discern the clinical impact of body fat distribution on mortality, including skin fold measurements, [33][34][35] bio-impedance, 36 sonographic depth, 37 and dual-energy X-ray absorptiometry.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the general population, obesity (BMI > 30) increases the risk of CKD, onset of albuminuria in CKD stages 1-2 as well as progression to CKD stages 3 and higher in the general population [18]. The course of CKD may be modulated by different causes of reduced kidney mass, genetic aspects, and metabolic phenotype.…”
Section: Obesity In the Early Stage Of Ckdmentioning
confidence: 99%
“…Obesity is associated with several important diseases that include type 2 diabetes, heart disease, stroke, asthma, cancer, chronic kidney disease, liver disease, all‐cause mortality, sciatica, low back pain, carpal tunnel syndrome . High BMI is also associated with a variety of psychological and neurological disorders, such as dementia, Alzheimer, suicide and other mental disorders .…”
Section: Introductionmentioning
confidence: 99%